Lyme Borreliosis in Primary Care: A Review of Current Diagnostic and Therapeutic Guidelines - Klusek, Mateusz; Franaszek, Jakub; Michalak, Karolina; Fahim, Knieszko; Przybył, Maciej; Jabrzyk, Martyna; Herchi, Nadia; Jarczyńska, Patrycja; Kijowski, Wojciech (Journal of Education, Health and Sport, 2026)
Introduction: Lyme disease is still a major public health problem and it can be easily misdiagnosed due to its broad symptomatology. The most recognizable specific sign is erythema migrans (EM) - a distinct skin lesion. However, EM does not appear in every patient with LD and most other signs are non-specific. For that reason, primary care physicians should know about proper history-taking and when laboratory testing can aid with the diagnosis as the earlier LD is diagnosed, the better the treatment outcome. Aim of the study: The aim of this study was to discuss the most recent literature on Lyme disease and extract information that is vital for primary care practice to support General Practitioners in navigating the difficulties that come with Lyme borreliosis. Materials and methods: This review of studies is based on articles available across major medical databases, namely PubMed and Google Scholar with a focus on papers from 2020 to 2026. Both domestic and international (USA, UK) guidelines were analysed. Key findings: The analysis reveals that a clinical diagnosis is possible when erythema migrans is present and that two-tiered serological testing is essential for disseminated stages. Guidelines outline antibiotic therapy regimens precisely and emphasise their high efficacy. Key findings highlight that post-treatment laboratory follow-up is not indicated. Moreover, effective management of Lyme disease includes careful history-taking (environmental exposure) and the administration of post-exposure prophylaxis when justified. Conclusion: Lyme disease is a public health issue and primary care physicians ought to have extensive knowledge on the diagnosis and treatment of the illness. Additionally, it is advised to educate the patients on disease transmission and prevention.